PENGARUH JENIS PELARUT DAN TEMPERATUR REAKSI PADA SINTESIS SURFAKTAN DARI ASAM OLEAT DAN n-METIL GLUKAMINA DENGAN KATALIS KIMIA - Jojor Rohana Oppusunggu; Vinta Rutliana Siregar; Zuhrina Masyithah (Jurnal Teknik Kimia USU, 2015)
Surfactants are molecules that also has a hydrophilic group and a lipophilic group that can unify a mixture consisting of water and oil. Alkanolamide is one type of nonionic surfactants are widely used in everyday life. In this study, will be observed the influence of the type of solvent and reaction temperature on the synthesis of surfactant alkanolamide n -methyl glukamine and oleic acid from palm oil with sodium methoxide catalyst. This study aims to determine the value of the hydrophilic lipophilic balance (HLB), pH and surface tension of surfactant, by observing the effect of the type of solvent and reaction temperature. This research was conducted by using a flask at 90 ° C, 110 ° C, 130 ° C for 3 hours reaction time, substrate ratio of 1: 2, the stirring speed of 150 rpm and a catalyst concentration of 0.4% (w/w). In the amidation reaction samples taken from the flask every 1 hour for 3 hours and then the results of this amidation reaction was washed with acetone solvent to separate the catalyst. Results washing then purified by heating at 90°C to evaporate the solvent surfactant products hexane and butanol. Results containing surfactant in the analysis with Hydrophilic Liphophilic Balance Method, surface tension and FT-IR spectrophotometry. Based on this research, the optimal conditions at a temperature of 110oC, reaction time 3 hours at the solvent ratio 2: 1. From the analysis of surfactant oleoil n-Methyl glukamine values obtained HLB in the range of 11,53 HLB in accordance with the standard detergent.